Thermodynamic Analysis of a Gas-Steam Combined Cycle Thermal Power Plant through Simulation with EES - Gordillo-Andía, Carlos; Tupayachy-Quispe, Danny; Almirón, Jonathan; Chavez, Belinda; Churata, Rossibel; Gordillo-Alarcon, Carlos (LACCEI, 2025)
The increasing global energy demand and concern for the environment have driven the search for more efficient and sustainable technologies for electricity generation. Among these, combined cycle thermal power plants have emerged as a prominent option thanks to their high efficiency and low emissions. This study focuses on the thermodynamic analysis of these plants, with the aim of optimizing their performance and minimizing their environmental impact. Through numerical simulations using the EES program, the behavior of different configurations and operating parameters has been evaluated. The results obtained show that the optimization of combined cycles is possible through a careful selection of variables such as the pressure ratio in the compressor, the inlet temperature to the turbine and the operating conditions of the heat recovery boiler. In addition, the importance of considering the impact of factors such as fuel quality and environmental conditions on the overall performance of the plant has been identified. This research contributes to the advancement of knowledge in the field of thermal energy and provides a valuable tool for power plant engineers and designers, allowing them to make more informed decisions and optimize the use of energy resources.